Drugs in R&D - van Rensburg, Anton
Drugs in R&D is an international, peer reviewed, open access, online only journal, and provides timely information from all phases of drug research and development that will inform clinical practice. Healthcare decision makers are thus provided with knowledge about the developing place of a drug in therapy. The Journal includes: Clinical research on new and established drugs; Preclinical research of direct relevance to clinical drug development; Short communications and case study reports that meet the above criteria will also be considered; Reviews may also be considered. Articles published in Drugs in R&D may be accompanied by plain language summaries, to assist patients, caregivers and others in understanding important medical advances.  The journal will consider fee discounts for developing countries and this is decided on a case by case basis. All manuscripts are subject to peer review by international experts. Letters to the Editor are welcomed and will be considered for publication.